PENGARUH DANA PIHAK KETIGA TERHADAP RENTABILITAS DAN LIKUIDITAS PADA BANK MANDIRI, BNI DAN BCA - Cut Srikandi; Luluk Kholisoh (Jurnal Ilmiah Ekonomi Bisnis, 2019)
The rapid growth of banking industry is inseparable from the number of new banks which increasing the fund mobility and credit allocation. This situation triggers competitive competition among banks to keep improving their financial performance. The continuous and significant decrease of bank perfomance will lead to financial distress or difficult circumstances, or it can be said to happen a bankruptcy threshold and it has a major impact on banking industry in general as well as Indonesia economic conditions in particular. Banks must be able to improve the profitability and liquidity levels in order to survive as one of the performance factors and banks health assessment and third party fund as one of the main source of funds. The aim of this research is to obtain an overview the extent influence of third party funds on profitability and liquidity level of the bank. The data used in this study is secondary data taken from quarterly financial statements from 2005-2008 and simple linear regression analysis.The results of this research which conducted at Mandiri, BNI, and BCA found that there was a significant influence between third party funds on profitability and liquidity. For BNI, there is a significant relationship between third party funds to ROA, ROE and NIM, but negative outcomes in BNI can be attributed to RR, although positive results are obtained at the LDR ratio. At BCA, a significant relationship is only obtained by ROE and NIM, while ROA is not. Positive relationships were also obtained by BCA for LDR and RR. Positive results were obtained by Bank Mandiri for all ROA, ROE and NIM ratios and LDR and RR, from the three banks Mandiri banks that had the best level of profitability and liquidity. The significant relation at BCA was only obtained by ROE dan NIM, but not ROA. The positive relation also can obtained toward LDR and RR at BCA. The positive result was obtained by Mandiri toward all ratio ROA, ROE and NIM as well as LDR and RR. In conclusion from those three banks, Mandiri bank has  the best level of profitability and liquidity.